2022
DOI: 10.3329/bjb.v51i3.61987
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conservation Tillage and Weed Management On Soil Microbial Community and Enzymatic Activity

Abstract: Conservation tillage and weed management practices were applied on maize-wheat cropping system to study the soil biological activities under Northern Himalayas region. The experiment included five tillage and three weed management treatments. Conservation agriculture (CA)-based management practices including residues incorporation (ZTR-ZTR), ZT-ZT, and ZT-ZTR showed higher soil microbial population (bacteria, fungi, and actinomycetes) and microbial activity during 2014-15 and 2015-16 in both maize and wheat cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…Studies have reported changes in the microbial community structures with the implementation of NT [11,60,61]. Other studies have found a non-significant effect on these structures [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported changes in the microbial community structures with the implementation of NT [11,60,61]. Other studies have found a non-significant effect on these structures [62,63].…”
Section: Discussionmentioning
confidence: 99%